1986
DOI: 10.1042/bj2330239
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stress and injury on the activity of phosphoenolpyruvate carboxykinase in the liver of the rat

Abstract: The effects of stress (diethyl ether anaesthesia for 4-8 min, or intravenous injection of 0.05 ml of a dimethyl sulphoxide/water mixture) and of a scald injury given under ether anaesthesia on hepatic PEPCK (phosphoenolpyruvate carboxykinase, EC 4.1.1.32) were studied in the post-absorptive rat. Injury raised PEPCK activity by about 70% in 2 h and by over 100% in 4 h, over three times as fast as in animals that had only been handled (controls). The two stresses, both of types commonly imposed in animal experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Values (Fig. 4) were higher in women than in men at ISS 4-8 (P<0.05) and [9][10][11][12][13][14] (P < 0.005), as expected,11 and rose with time after injury at ISS [4][5][6][7][8][9][10][11][12][13][14] [adrenaline] had been measured in them. The residuals were, however, very non-normally distributed.…”
Section: Preliminary Observationssupporting
confidence: 62%
See 2 more Smart Citations
“…Values (Fig. 4) were higher in women than in men at ISS 4-8 (P<0.05) and [9][10][11][12][13][14] (P < 0.005), as expected,11 and rose with time after injury at ISS [4][5][6][7][8][9][10][11][12][13][14] [adrenaline] had been measured in them. The residuals were, however, very non-normally distributed.…”
Section: Preliminary Observationssupporting
confidence: 62%
“…2), which were measured within the fairly narrow bands of injury severity shown. These, suggested by Copes et al,13 correspond to minor (ISS 1-3), moderate (4)(5)(6)(7)(8), severe (9)(10)(11)(12)(13)(14), very severe (16)(17)(18)(19)(20)(21)(22)(23)(24) and life-threatening (25+) injuries. Success has been measured by the percentage of the variance within each group that can be accounted for by the various factors.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Of these, adrenaline seems to play the major role after injury, since the resultant hyperglycaemia is fairly closely related to plasma adrenaline concentrations . Glucagon secretion after injury is largely 8-adrenergically mediated (Porte & Robertson, 1973;Lindsey et al, 1975;Rose & Heath, 1986) and so might be involved in this relationship, but several studies have shown that glucagon secretion responds relatively slowly to injury (e.g. Meguid el al., 1972; Giddings et al, 1976; see also Fig.…”
Section: Licer and Muscle Glycogenmentioning
confidence: 99%